Physicochemical characteristics and in vitro digestibility of starches from colored quinoa (Chenopodium quinoa) varieties. Issue 5 (1st April 2022) - Peng, Mingjun; Yin, Lisha; Dong, Jilin; Shen, Ruiling; Zhu, Yingying
Abstract : Abstract: The quinoa flour processing is mostly subject to the properties of starch. Starches from four colored quinoa varieties, including white quinoa (QS‐W), yellow quinoa (QS‐Y), red (QS‐R), and black (QS‐B), were compared with respect to their physicochemical properties and in vitro digestibility. Results indicated that QS‐B exhibited the highest content of amylose (8.14%) ( p  < 0.05). All starch samples exhibited as irregular sphere with a particle size less than 3 µm. Results of the FT‐IR and X‐ray showed that the short‐range order of the four quinoa starches exhibited no significant difference; all starches showed a typical A‐type diffractrometric pattern and was not affected by seed color, and QS‐Y had the highest relative crystallinity (34.3%) ( p  < 0.05). In addition, QS‐W reflected the highest solubility (6.32%) and QS‐Y showed the highest swelling power (19.45 g/g) ( p  < 0.05). QS‐Y also presented a higher Δ H value (11.46 J/g) ( p  <  0.05 ), while QS‐R peak temperature and peak G ʹ were the lowest. Besides, QS‐B had the highest slow‐digestible starch (SDS) and resistant starch (RS) content, while the lowest estimated glycemic index (eGI) value ( p  < 0.05). Also, there was a negative correlation between hydrolysis rates and amylose content of quinoa starch. Practical Application: Due to the low gelatinization temperature of quinoa starch, it can be used to both produce and improve instant and fast food products. Quinoa starch particles are small, and Pickering emulsions and additives have potential application values. Red quinoa contains easily digestible starch, which can be a good food choice for infants and the elderly, while white quinoa starch has less swelling power and can be used in noodle products. The results of this study can help to underpin the study of quinoa nonstarch components versus starch component.